Application of persulfate salts for enhancing UV disinfection in marine waters. (15th October 2019) - Moreno-Andrés, Javier; Farinango, Gonzalo; Romero-Martínez, Leonardo; Acevedo-Merino, Asunción; Nebot, Enrique
Abstract: Over the years, industrial activities that generate high salinity effluents have been intensifying; this has relevant potential for causing organic and microbiological pollution which damages both human and ocean health. The development of new regulations, such as ballast water convention, encourage the development of treatment systems that can be feasible for treating seawater effluents. Accordingly, an approach based on the UV activation of persulfate salts has been assessed. In this scenario, two different persulfate sources (S2 O8 2− and HSO5 − ) were evaluated under UV-C irradiation for disinfection purposes. An optimization process was performed with low chemical doses (<1 mM). In order to extensively examine the applicability on seawater, different water matrices were tested as well as different microorganisms including both fecal and marine bacteria. An enhancement of UV-inactivation with the addition of persulfate salts was achieved in all cases, kinetic rate constant has been accelerated by up to 79% in seawater. It implies a UV-dose saving up to 45% to achieve 4-log reductions. Best efficiencies were obtained with [HSO5 − ] = 0.005 mM and [S2 O8 2− ] = 0.5 mM. Higher effectiveness was obtained with the use of HSO5 − due to its low stability and interaction with chloride. Also, different responses were obtained according to the specific microorganisms by achieving faster disinfection in Gram-negative than in Gram-positive bacteria, the sensitivity observed was Vibrio spp. > E. coli > E. faecalis ≈ Marine Heterotrophic Bacteria. With an evaluation of regrowth after treatment, greater cell damage was detected with the addition of persulfate salts. The major ability of regrowth for marine bacteria encourages the use of a residual disinfectant after disinfection processes. Graphical abstract: Image 1 Highlights: Photolytic activation of persulfate salts has been assessed for seawater disinfection. Both sources of persulfate enhance UV disinfection in different water matrices. The lower stability of PMS facilitates the interaction with chlorides in marine water. Major sensitivity has been detected for Gram-negative bacteria in all tested systems. Higher ability for regrowth has been detected for natural occurring bacteria.